2023
DOI: 10.52852/tcncyh.v161i12e11.1121
|View full text |Cite
|
Sign up to set email alerts
|

Common adverse events following immunization with moderna Covid-19 vaccine among Vietnamese adults at Hanoi Medical University in 2021

Abstract: The rapid creation of vaccinations has increased the risk of vaccine safety. In less than two years, a significant number of COVID-19 vaccines were developed and approved in various countries to control the COVID-19 pandemic. This study was conducted to identify the common adverse events following immunization with mRNA-1273 (Moderna COVID-19) vaccine among adults in 2021. A cross-sectional study using randomized sampling was conducted in Hanoi, Vietnam, with 766 participants. The results show that the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first study in Vietnam that provides safety data on various combined vaccination strategies for COVID-19 prevention. While previous studies in Vietnam considered the safety of two matching doses of Pfizer [ 12 ], Moderna [ 13 ] vaccines, or a single dose [ 16 ], this study delves deeper into the safety implications of combining different types of vaccines for the second booster dose. The study confirmed previous evidence on the safety of mixed COVID-19 vaccines [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the present study is the first study in Vietnam that provides safety data on various combined vaccination strategies for COVID-19 prevention. While previous studies in Vietnam considered the safety of two matching doses of Pfizer [ 12 ], Moderna [ 13 ] vaccines, or a single dose [ 16 ], this study delves deeper into the safety implications of combining different types of vaccines for the second booster dose. The study confirmed previous evidence on the safety of mixed COVID-19 vaccines [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence in Vietnam suggested that the matching of the same COVID-19 vaccine for a booster is safe with the PfizerBioNTech [ 12 ] or mRNA-1273 (Moderna) [ 13 ]. Less is known about the safety of mixed doses between different vaccines in two doses of vaccination [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation